THE EFFECT OF DIGITAL LITERACY AND ENTREPRENEURS LEARNING ON STUDENTS' ENTREPRENEURIAL INTENTION - Maudina, Anissa; Saptono, Ari; Pratama, Aditya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
The number of unemployed is always increasing every year, especially in high school graduates. One way to overcome this is to become an entrepreneur. This study aims to determine the effect of digital literacy and the quality of entrepreneurship learning on students' entrepreneurial intentions. The research population is class XI students in the 2020/2021 academic year at SMAN 35 Jakarta and SMAN 7 Jakarta, totally 454 students. Sampling was carried out using the Slovin formula with a total sample of 212 students. Data collection techniques using questionnaires and data analysis techniques using descriptive statistical analysis and multiple linear regression analysis with the help of the IBM SPSS 25.0 program. The results showed that there was a positive and significant influence between Digital Literacy and Entrepreneurship Learning Quality on Students' Entrepreneurial Intentions. The level of digital literacy is very high, while the level of quality of entrepreneurship learning is medium and the level of entrepreneurial intention is very high. It can be concluded that in the current digital era, the need for digital literacy skills is needed to support students' intentions in starting entrepreneurship as well.